Clinical and cortical decline in the aphasic variant of Alzheimer's disease. Issue 4 (11th February 2019) - Rogalski, Emily Joy; Sridhar, Jaiashre; Martersteck, Adam; Rader, Benjamin; Cobia, Derin; Arora, Anupa K.; Fought, Angela J.; Bigio, Eileen H.; Weintraub, Sandra; Mesulam, Marek‐Marsel; Rademaker, Alfred
Abstract: Introduction: Primary progressive aphasia (PPA) displays variable progression trajectories that require further elucidation. Methods: Longitudinal quantitation of atrophy and language over 12 months was completed for PPA patients with and without positive amyloid PET (PPA Aβ+ and PPA Aβ− ), an imaging biomarker of underlying Alzheimer's disease. Results: Over 12 months, both PPA groups showed significantly greater cortical atrophy rates in the left versus right hemisphere, with a more widespread pattern in PPA Aβ+ . The PPA Aβ+ group also showed greater decline in performance on most language tasks. There was no obligatory relationship between the logopenic PPA variant and amyloid status. Effect sizes from quantitative MRI data were more robust than neuropsychological metrics. Discussion: Preferential language network neurodegeneration is present in PPA irrespective of amyloid status. Clinical and anatomical progression appears to differ for PPA due to Alzheimer's disease versus non–Alzheimer's disease neuropathology, a distinction that may help to inform prognosis and the design of intervention trials.